Environmentally Friendly Integrated Waste Management Strategy in Rantepao District - Restu Dalame; Idawarni J. Asmal; Ria Wikantari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to find out how the solid waste system in Rantepao District is, how much household waste is produced in Rantepao District, and how is an environmentally friendly integrated waste management strategy through waste infrastructure planning in Rantepao District. A sample of 100 respondents' families in each Kelurahan and Lembang in Rantepao District, North Toraja Regency. The data was collected through field research by taking samples and interviews with respondents as well as library research. Data were analyzed using a combination of qualitative and quantitative methods. The results showed that: 1) The solid waste system in Rantepao Subdistrict did not meet the criteria set by government regulations and the National Standardization Body. It is known that this settlement does not have a TPS and must dispose of its waste to Enrekang Regency so that facilities such as garbage carts also need to be added. The condition of the trash containers/bins in the houses of the dominant residents is not in good condition. And the dominant community throws their household waste directly into public places such as rivers and markets. 2) The composition of waste consists of 58% organic waste, while 42% of non-organic waste. It is known that the total average weight of household waste generated for a day in Rantepao District is 11,441.76 Kg/day or 0.48 Kg/person/day and the volume is 125,144.25 Liters/day or 5.25 Liters/person. /day. 3) It takes 98 manual transport carts with a standard length of 160 cm x width 80 cm x height 100 cm or 1,280 liters to support the waste management strategy by collecting waste from the source at least once a day. Procurement of two TPS 3R model 2 in vacant land locations in Rantepao and Lembang Limbong Villages as a planning recommendation as shown in Figures 5.4.1 and 5.4.2. The recommendations from this research are 1) One way that can be done to improve the solid waste system in Rantepao District is the distribution of proper trash cans in each resident's house, by separating organic and non-organic waste from the source. 2) It is necessary to educate the community about 3R waste processing (reduce, reuse, and recycle) and carry out mutual cooperation activities to clean markets and rivers. 3) The provision of facilities and infrastructure as well as the implementation of 3R TPS must be supported by the local government to reduce river pollution by household waste generated by the people of Rantepao District.